2014
DOI: 10.14233/ajchem.2014.15346
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Characterization of Gum from Cordia myxa

Abstract: Cordia is a genus of flowering plants in FamilyBoraginaceae. There are about 250 species in this genus 1 which are found mostly in warm climate. Four species namely, C. dichotoma, C. latifolia, C. Abyssinia and C. myxa, are explored up to a certain extent for various applications in scientific literature 2-6 . However, in general this potentially beneficial plant resource has remained unexplored. Our research group has recently reported the successful application of gum cordia to retard the oxidation in nuts [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
1
7
1
Order By: Relevance
“…Xu et al [29] modified the polysaccharides extracted from Ganoderma lucidum that resulted in the drastic boost in antioxidant behavior. These results are in strong agreement with the outcomes of Haq et al [30] who investigated gum C. myxa for extraction and characterization. These modified polymers exhibited excellent hydroxyl free radical scavenging activity (83.4 %) while the simple polysaccharide showed hydroxyl scavenging activity up to 42.9 %.…”
Section: Resultssupporting
confidence: 92%
“…Xu et al [29] modified the polysaccharides extracted from Ganoderma lucidum that resulted in the drastic boost in antioxidant behavior. These results are in strong agreement with the outcomes of Haq et al [30] who investigated gum C. myxa for extraction and characterization. These modified polymers exhibited excellent hydroxyl free radical scavenging activity (83.4 %) while the simple polysaccharide showed hydroxyl scavenging activity up to 42.9 %.…”
Section: Resultssupporting
confidence: 92%
“…It is reported by von Borries–Medrano, et al [ 35 ] that starches become more susceptible to short term retrogradation in the presence gaur gum. Similar phenomenon could have resulted in the higher setback values of corn starch due to gum Cordia , because the gum Cordia hydrocolloid is dominated by galactomannan fraction [ 36 ]. Short-term retrogradation is affected by several factors including the amylose content, the size of the amylose molecules, and the dispersion of amylose chains in the gel matrix [ 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, it is estimated that the formation of gum Cordia consists of three parts with different molecular weights. Haq et al [9] observed two peaks related to gum by the GPC method, showing the average molar mass of 1.81 × 10 6 and 3.89 × 10 3 g•mol −1 . Usually, the average molar mass of the first fraction in gums with a plant base is about 10 5 g•mol −1 , which is almost lower than the amount for gum Cordia.…”
Section: Molecular Informationmentioning
confidence: 99%
“…is genus with almost 250 species generally grows in warm regions. C. latifolia, C. myxa, C. dichotoma, and C. abyssinia are the four species of Cordia which are considered advantageous for a number of applications in different scientific articles [9]. Cordia is found in tropical and subtropical zones of Africa, America, Oceania, and Asia [10].…”
Section: Introductionmentioning
confidence: 99%